Models of liquid storage tanks - Ismail, KAR; Leal, JFB; Zanardi, M. A. (Elsevier B.V., 1997)
We present the results of a comparative study on thermally stratified tanks for hot storage. A two-dimensional model is employed. A numerical solution was obtained using the control-volume technique due to Patankar. The two-dimensional model was simplified for the pure conduction case. Results from the two models were compared with each other and with available numerical and experimental results. (C) 1997 Elsevier B.V. Ltd.